2019
DOI: 10.18699/vj19.496
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of grain quality parameters for winter rye breeding

Abstract: The purpose of this work was to evaluate the phenotypic variability of grain quality indicators and to identify the set of the most informative indicators for the selection of different use varieties of winter rye. The research was carried out in Tatar Scientific Research Institute of Agriculture – Subdivision of the “Kazan Scientific Center of Russian Academy of Sciences” in 2001–2015 on 15 varieties of winter rye. Twenty parameters defining quality of grain and raw value were estimated: technological indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…For instance, in Europe, more than 41% of the total winter rye crop is used for food, 32% for fodder, and about 27% for other purposes [1]. In Russia, more than half of winter rye grain is used for the production of flour [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Europe, more than 41% of the total winter rye crop is used for food, 32% for fodder, and about 27% for other purposes [1]. In Russia, more than half of winter rye grain is used for the production of flour [2].…”
Section: Introductionmentioning
confidence: 99%
“…After low-temperature adaptation, where plants are exposed to low but non-freezing temperatures, rye can withstand low negative temperatures down to about −30 • C [21]. Other researchers have found that the frost resistance of rye acquired during cold acclimatization reaches −23 • C compared to wheat (−19 • C), triticale (−16 • C), and barley (−13 • C) [22]. According to the observations of I. Tumanov [23], even in winters with little snow, rye is able to tolerate frosts down to −25 • C-−35 • C. Resistance to low negative temperatures and to the complex of unfavorable environmental factors will vary considerably depending on the variety specificity.…”
Section: Introductionmentioning
confidence: 99%